Advances in Monetary Policy Design : Applications to the Gulf Monetary Union. - Barnett, William A. (Cambridge Scholars Publishing, 2013)
In response to the recent financial crisis, many countries have initiated monetary stimulus packages. Maintaining proper measures of monetary aggregates is of particular importance for such economic policies. However, many central banks worldwide use the simple-sum monetary indexes, which ignore the liquidity characteristics of financial assets. Using the simple-sum indexes can produce misleading information, especially for broad monetary aggregates within which financial assets are not likel ...